Komunikasi Efektif Pada Anak Usia Dini - Musrifah, Musrifah (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Abstract: One of the developmental tasks that must be completed in early childhood is language development. Often we meet early childhood biologically well-developed but not yet well developed developmental tasks. Language skills do not just come, but like other abilities, they must be able to be grown and built so that they are in accordance with the proper stage of development. Like other abilities, language skills are created from biological genetic factors as the bricks and environmental factors as the architect. Not a few teachers and guardians of students who experience serious problems in communicating with early childhood because of the lack of understanding of the way of thinking and learning of early childhood that affects their language development. In order to communicate effectively with early childhood, teachers and parents need to understand the character of the child's language and help children develop their language skills. Teachers and parents need to explore, exemplify, motivate, and facilitate language games so that early childhood can communicate effectively and confidently, both with themselves and with others.